Engineering sulfur vacancies and impurities in NiCo2S4 nanostructures toward optimal supercapacitive performance. (August 2016) - Lu, Fei; Zhou, Min; Li, Wanrong; Weng, Qunhong; Li, Cuiling; Xue, Yanming; Jiang, Xiangfen; Zeng, Xianghua; Bando, Yoshio; Golberg, Dmitri
Abstract: High efficiency supercapacitors require the electrode materials which integrate high specific capacitance, favorable rate capability and long-term cyclic stability. These features are often associated with vacancies and impurities in the electrodes. Understanding the mechanism behind the related process provides a deep insight into improved supercapacitive performance. Here we present the synthesis of spinel structured nickel cobalt sulfide (NiCo2 S4 ) nanomaterials with tunable sulfur vacancy concentrations and impurities by controlling the sulfurization process. The effects of these defects on the nanomaterial supercapacitive properties were then clearly identified. Interestingly, on one hand, the sulfur vacancies were found to increase the specific capacitance by improving electrical conductivity, while, on the other hand, they hindered the rate capability and cyclic stability due to the increased crystal structure disordering. An optimal supercapacitive performance was achieved, namely, high specific capacitance, favorable rate capability and long-term cyclic stability were documented for both three-electrode system and solid-state asymmetric supercapacitor device. These results have significant implications for the design and optimization of pseudocapacitive properties of transition metal compounds. Graphical abstract: Highlights: A facile route was employed to engineer the sulfur vacancies and impurities in NiCo2 S4 . Effects of sulfur vacancies and impurities on the nanomaterial supercapacitive properties were clearly identified. An optimal supercapacitive performance integrating high specific capacitance, favorable rate capability and long-term cyclic stability was achieved.